EPIDEMIOLOGY OF THE PEDIATRIC EYE INJURIES IN THE SUGHD REGION OF TAJIKISTAN - KH.J. KARIM-ZADE; N.A. OCHILZODA; Z.A. DADОBOEV (Avicenna Tajik State Medical University, 2020)
Objective: To study epidemiology and clinical features of of eye injuries in children in Sughd Region of the Republic of Tajikistan from 1993 up to 2013. Methods: A retrospective analysis of 616 (622 eyes) children with eye injuries required in-patient treatment in the Eye Department of Regional Clinical Hospital of Sughd Region was conducted for 20 years from 1993 to 2013. Results: For observable period in 616 children with eye injuries, who got in-patient treatment, the level of incidence was 6.6 per 100 000 children's population of the region. Mean age was 7.7 (range from 1 to 15 years), male/female ratio was 2.8:1. Children aged 3-10 were most affected to injuries. Eye blunt trauma was diagnosed in 168 eyes (27%), open globe injuries in 429 (69%), eyelid injuries in 25 patients (4%). Visual acuity improvement (0.5-1.0) noted in 24.6%, moderate decrease of visual acuity (0.2-0.4) - in 12.9%, low vision (0.05-0.1) - in 7.9% and blindness (0-0.04) in 23% of cases. Factors, associated with unfavorable visual outcome were vitreous hemorrhage, hyphema, cataract and endophthalmitis. Conclusion: According to the results of the study, pediatric eye injuries are important causes of monocular blindness and impaired vision. In spite of improving possibilities of healthcare and treatment, in our study, one-third of children suffer from blindness and impaired vision, as a result of injuries, which indicates the need to develop and implement preventive and treatment measures in order to achieve the most favorable results of the injury.